South Africa: Agrimark Trends (AMT) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Agrimark Trends (AMT) provides a one-stop-shop for agricultural market information to enable South African farmers to make informed decisions.